El meme como recurso didáctico para enseñar ortografía a estudiantes de noveno año, de Educación General Básica Superior, de la Unidad Educativa “Mons. Luis Alfonso Crespo Chiriboga” - Pintado Jumbo, Yajaira Maribel (2024)
The present investigation focuses on analyzing the use of the meme as a didactic resource to teach spelling to students in the ninth year of Higher General Basic Education. The research, with a qualitative approach, seeks to obtain the participants' perspectives throughout 9 sessions of pedagogical intervention. The objectives include inquiring about the students' spelling skills, applying the meme as a teaching resource, evaluating its effectiveness, and determining the students' attitudes towards this innovation. The results show that the meme, in addition to being innovative, is effective in improving comprehension and retention of spelling rules. The favorable reception by the students who were interviewed suggests that the meme not only breaks the monotony, but also contributes to a dynamic learning environment. The assessment of spelling skills through a diagnostic evaluation reveals tendencies to make recurrent errors, especially in the confusion between letters, omission of the tilde and absence of punctuation marks. The pedagogical intervention with memes as a didactic resource proves effective in addressing these deficiencies, providing an innovative approach that captures attention and facilitates the understanding of spelling rules. The integration of humorous and visual elements not only increases participation and attention, but also improves spelling skills. The final evaluation confirms noticeable progress, consolidating the meme as an effective didactic resource in teaching spelling. In summary, this study underlines the importance and effectiveness of the meme in improving the spelling competence of students in the ninth year of Higher General Basic Education.